2008
DOI: 10.1088/0957-4484/19/34/345201
|View full text |Cite
|
Sign up to set email alerts
|

Localized surface plasmon-induced emission enhancement of a green light-emitting diode

Abstract: The output enhancement of a green InGaN/GaN quantum-well (QW) light-emitting diode (LED) through the coupling of a QW with localized surface plasmons (LSPs), which are generated on Ag nanostructures on the top of the device, is demonstrated. The suitable Ag nanostructures for generating LSPs of resonance energies around the LED wavelength are formed by controlling the Ag deposition thickness and the post-thermal-annealing condition. With a 20 mA current injected onto the LED, enhancements of up to 150% in elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
107
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(110 citation statements)
references
References 14 publications
2
107
0
Order By: Relevance
“…SP can achieve a great enhancement of the light field in a small scale to achieve the purpose of scattering enhancement [143]. Besides SERS, another important form of weak coupling is the SP-induced enhancement of molecular fluorescence, which is divided into SP-coupled emission enhancement (SPCE) [144] and SP-induced absorption enhancement [145], respectively. Nowadays, the study of SPCE characterizes steady-state spectroscopy.…”
Section: Weak Exciton-plasmon Couplingmentioning
confidence: 99%
“…SP can achieve a great enhancement of the light field in a small scale to achieve the purpose of scattering enhancement [143]. Besides SERS, another important form of weak coupling is the SP-induced enhancement of molecular fluorescence, which is divided into SP-coupled emission enhancement (SPCE) [144] and SP-induced absorption enhancement [145], respectively. Nowadays, the study of SPCE characterizes steady-state spectroscopy.…”
Section: Weak Exciton-plasmon Couplingmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Such a nanophotonic approach has been applied to light emitting devices. [15][16][17][18][19][20][21][22]24,25 The rationale behind is that the transfer of energy from carriers in GaInN QW into localized optical plasmon supported by the metallic nanostructures will create an a afad@fotonik.dtu. additional light emission channel called plasmonic channel.…”
Section: Introductionmentioning
confidence: 99%
“…17 For a larger D of approximately 70 nm, the green emission output power based on the plasmonic coupling of the metals with active layer has been improved by approximately 90-220% with contribution from both IQE and light extraction efficiency. 16 It is also very interesting to note that the photoluminescence (PL) intensity of the green GaInN QW has been improved by a factor of 4.8 using periodic nanocylinders with a 5 nm spacing layer. 20 It has been shown that for very large D ∼200 nm, a 26% improvement of the optical output power due to enhanced light scattering can be achieved without benefits from plasmon enhanced IQE.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] One of them consists in using metallic structures to enhance the radiative rate thanks to the surface plasmons they support. 6,7 These plasmon modes have a high local density of states, and consequently catch the main part of the emission, which can then be coupled to radiative light with a corrugation (either periodic 6 or not 8,9 ). Luminescence enhancements of up to 15 have been demonstrated with these processes.…”
mentioning
confidence: 99%